Concordant patterns of morphological, stable isotope and genetic variation in a recent ecological radiation (Salmonidae: Coregonus spp.). Issue 17 (19th July 2022) - Bernal, Moisés A.; Yule, Daniel L.; Stott, Wendylee; Evrard, Lori; Dowling, Thomas E.; Krabbenhoft, Trevor J.
Abstract: Groups of sympatric taxa with low interspecific genetic differentiation, but considerable ecological differences, offer great opportunities to study the dynamics of divergence and speciation. This is the case of ciscoes ( Coregonus spp.) in the Laurentian Great Lakes, which are characterized by a complex evolutionary history and are commonly described as having undergone an adaptive radiation. In this study, morphometrics, stable isotopes and transcriptome sequencing were used to study the relationships within the Coregonus artedi complex in western Lake Superior. We observed general concordance for morphological, ecological and genomic variation, but the last was more taxonomically informative as it showed less overlap among species in multivariate space. Low levels of genetic differentiation were observed between individuals morphologically identified as Coregonus hoyi and C. zenithicus, which could be evidence of incomplete lineage sorting or recent hybridization between the two groups. Transcriptome‐based single nucleotide polymorphisms exhibited significant divergence for genes associated with vision, development, metabolism and immunity among species that occupy different habitats. This study highlights the importance of using an integrative approach when studying groups of taxa with a complex evolutionary history, as individual‐level analyses of multiple independent data sets can provide a clearer picture of the patterns and processes associated with the origins of biodiversity.